Assessing the delivery efficacy and internalization route of cell-penetrating peptides. - Andaloussi, S; Guterstam, P; Langel, U (2007)
Developing efficient delivery vectors for bioactive molecules is of great importance within both traditional and novel drug development, such as oligonucleotide (ON)-based therapeutics. To address delivery efficiency using cell-penetrating peptides (CPPs), we here present a protocol based on splice correction utilizing both neutral and anionic antisense ONs, either covalently conjugated via a disulfide bridge or non-covalently complexed, respectively, that generates positive readout in the form of luciferase expression. The decisive advantage of using splice correction for evaluation of CPPs is that the ON induces a biological response in contrast to traditionally used methods, for example, fluorescently labeled peptides. An emerging number of studies emphasize the role of endocytosis in translocation of CPPs, and this protocol is also utilized to determine the relative contribution of different endocytic pathways in the uptake of CPPs, which provides valuable information for future design of novel, more potent CPPs for bioactive cargoes.